2006
DOI: 10.1073/pnas.0511306103
|View full text |Cite
|
Sign up to set email alerts
|

Tumor endothelial marker 1 ( Tem1 ) functions in the growth and progression of abdominal tumors

Abstract: Tumor endothelial marker 1 (Tem1; endosialin) is the prototypical member of a family of genes expressed in the stroma of tumors. To assess the functional role of Tem1, we disrupted the Tem1 gene in mice by targeted homologous recombination. Tem1 ؊/؊ mice were healthy, their wound healing was normal, and tumors grew normally when implanted in s.c. sites. However, there was a striking reduction in tumor growth, invasiveness, and metastasis after transplantation of tumors to abdominal sites in mice without functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 31 publications
12
158
2
Order By: Relevance
“…This results in an increase in CD248 expression, via hypoxia inducible factor-2a [9], which in turn is required for full expansion of pLN. This is analogous to the previous studies where lack of CD248 inhibited full expansion of abdominal tumours [8]. …”
supporting
confidence: 90%
“…This results in an increase in CD248 expression, via hypoxia inducible factor-2a [9], which in turn is required for full expansion of pLN. This is analogous to the previous studies where lack of CD248 inhibited full expansion of abdominal tumours [8]. …”
supporting
confidence: 90%
“…Similarly, in situ hybridization analysis has demonstrated an upregulation of endosialin mRNAs in the tumor vasculature but again this method cannot distinguish between an endothelial and perivascular localization of the signal. 5,14,17 As endosialin is also expressed in the developing vasculature, different laboratories have performed double labeling of cryosections both from tumors and developing tissues. However, disparate results have been obtained in that it has been reported that endosialin is only expressed on the endothelial cells, 12 only on the pericytes 9,13,18 and on both.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of these findings is twofold. First, mice with a homozygous deletion in endosialin (Cd248) show impaired growth, invasion and vascularization of implanted abdominal tumors, 17 suggesting that endosialin expression on pericytes has an important functional role in the tumor vasculature. Second, there is increasing evidence that antiangiogenic therapies targeting both endothelial cells and pericytes are more effective than single-agent therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Although not expressed by endothelium (MacFadyen et al, 2005), TEM1/endosialin mediates tumor, but not developmental angiogenesis. Thus, orthotopically implanted colon tumors grow slower in the TEM1/endosialin À/À mouse, whereas developmental angiogenesis is normal (Nanda et al, 2006). Endothelial-specific expression of CLE-C14A and functional studies now confirm a role for this type 14 C-type lectin family member in vascular biology.…”
Section: Clec14a Is a Novel Tumor Endothelial Markermentioning
confidence: 90%